PENGARUH PAJAK TANGGUHAN, KOMPENSANSI MANAJEMEN DAN INTENSITAS PERSEDIAAN TERHADAP MANAJEMEN PAJAK - Astiar Rahmania; Nuraini Yusuf (Publika Citra Media, 2026)
This research aims to find out and analyze the effects of deferred tax, managementcompensation, inventory intensity on property and real estate sector companies listedon the Indonesia Stock Exchange for the period 2019 - 2023. This type of research isquantitative research, using secondary data. The data analysis methods used aredescriptive statistical tests, panel data model analysis, classical assumption tests andhypothesis tests using Microsoft Excel and E-Views 12 applications. The populationin this research is property and real estate sector companies listed on the IndonesiaStock Exchange for the period 2019 - 2023. The data collection technique in thisresearch is a purposive sampling technique with a total of 94 populations, so that thedata samples obtained in this research are 8 samples. The results of the rearch showthat deferred tax, management compensation, inventory intensity simultaneouslyaffect tax management.. Then, the results obtained show partially stated that deferredtax had no effect on tax management, management compensation had no effect on taxmanagement, inventory intensity had no effect on tax management.